Upaya Meningkatkan Keterampilan Passing Sepak Bola dengan Gaya Mengajar Cooperative Learning - nanang nanag (Sport Pedagogy Journal, 2023)
This study aims to Improve Football Passing Skills with Teaching Style Cooperative Learning in Grade VII A Students of SMP Negeri 1 Sanggau Ledo, Bengkayang Regency. The method used in this research is descriptive method, while the type of research is classroom action research. The research tool used is the Attitude Process, Observation Sheet. Sources of data in this study were teachers and students, research data in the form of findings during observations from the work of students that had been collected. Then processed qualitatively, this data analysis was carried out in a quantitative descriptive manner based on the results of observations of activities and learning outcomes. The results showed that from Pracyclus 34.48%, Cycle I 68.96% and Cycle II 86.20%. The minimum completeness criterion is 75. So it can be interpreted that there is an increase in football passing skills with a cooperative learning teaching style in class VII A students at SMP Negeri 1 Sanggau Ledo, Bengkayang Regency.